Effectiveness and safety of tranexamic acid in total joint arthroplasty. Issue 11 (November 2019) - Yaghmour, Khaled M.; Atkinson, Sam; Chisari, Emanuele; McDonnell, Stephen M.; Khan, Wasim
Total joint arthroplasty is associated with significant blood loss, that could result in the need of blood transfusions. Several techniques are being utilised to limit the volume of blood loss, in order to avoid transfusion. In this review, we look at blood loss in total joint arthroplasty and the perioperative strategies to limit the loss of blood. With the use of tranexamic acid gaining popularity, we analyse the published literature on its use in patients undergoing total joint arthroplasty. We have found that published studies favour using tranexamic acid in total joint arthroplasty as a safe and effective method of reducing blood loss.